The Use of English in an Islamic Boarding School in Indonesia (students’ perspective) - Damayanti, Fury Yulia; Purwaningtyas , Titin (Yayasan Marwah Madani Riau, 2026)
In the most Islamic boarding school setting in Indonesia, all students are required to master the English language for their daily interaction. Not only in their subjects, but English is also used in their daily conversations, in some competitions, and on written signs at the school. The present study seeks to discover the students’ perspective on English language use in the Islamic boarding school in East Java. The participants of this study were the senior high school students. Informed by qualitative research, data were collected by interviews and analyzed the data involving data collection, data reduction, data display, and data conclusion (Miles, Huberman & Saldana, 2014). The goal of the study is to know how English is taught in Islamic boarding schools and the students’ perspective on the use of English in Islamic boarding schools. The result showed that they use English not only in class but also out of class. The students used English because of the rules that obliged them to use English, and some challenges in using English in an Islamic boarding school. Especially the lack of vocabulary and how to pronounce words well. Furthermore, the implications of this study for teachers and stakeholders in Islamic boarding schools in order to improve better in teaching of English. Key Words: ELT, Islamic boarding school, students’ perception